Cytogenetic anomalies of winter wheat cells, induced by chemical contamination of the territory of Kalush industrial district - V. V. Morgun; R. A. Yakymchuk (Regulatory Mechanisms in Biosystems, 2018)
Mass accumulation of toxic waste near inhabited localities has changed some regions of Ukraine, in particular Kalush industrial area (Ivano-Frankivsk region), into zones of ecological disaster. Research on cytogenetic anomalies caused by chemical soil contamination of the territories of toxic chemical warehouses will be useful in determining the level of mutagenic activity of xenobiotics when they enter the environment and potential mechanisms of the induction of chromosome reconstructions by them and mitosis disorders. The aim of the research is to study frequency and spectrum of the types of cytogenetic disorders in T. aestivum L. under the prolonged effect on the seeds of soil contaminated with hexachlorinebenzene from territories of toxic waste warehousing and to determine the level of their mutagenic activity as compared with the effect of moderate and high concentrations of N-nitrozo-N-methylurea (NMU). Seeds of winter wheat cultivars Al’batros odes’kyi and Zymoiarka were sprouted in the soil samples taken from the toxic waste ground of LLC “Oriana Halev”, its recultivated area and the dump area of Dombrovskyi potash ore mine, situated near Kalush city. Hexachlorobenzene concentrations in the soil of the studied areas exceeded CPC by 1233–18350 times. Soil samples from a tentatively clean area of Svatky village, Hadiach district, Poltava region were taken as the control. To study cytogenetic consequences of the effect of moderate and high concentrations of NMU, wheat seeds were kept in a mutagen water solution at concentrations 0.005%, 0.010%, 0.025%. Frequency and spectrum of cytogenetic anomalies were determined in the cells of sprout root meristem using the anatelophase technique. Chemical contamination of the soil exhibited high mutagenic activity which, by induction frequency of cytogenetic anomalies, exceeded the control level by 1.8–3.8 times and equalled mutagenic activity of NMU in moderate concentrations. The highest level of cytogenetic disorders, which exceeded spontaneous indicators by 3.4–3.8 times, was found when the soil contamination of the territory of the toxic waste ground with hexachlorobenzene was the most intensive. Traces of hexachlorobenzene in the soil of the recultivated plot of the ground continue to manifest high cytogenetic activity and pose a threat for the genomes of living organisms. Frequency of chromosome aberrations at a low hexachlorobenzene concentration in the soil of the disposal area of Dombrovskyi mine exceeded spontaneous indicators by 1.8–2.4 times, which is the result of its complex effect with natural-mineral compounds of mining-chemical raw materials. The increase of some bridges and acentric chromosome rings – markers of a radiation effect – among the types of cytogenetic disorders, induced by the soil contamination with hexachlorobenzene, confirms the radiometric properties of the xenobiotic, which were identified at high concentrations of NMU. The increase in the number of the cells with multiple aberrations, induced by the hexachlorоbenzene contamination of the soil holding the studied objects proves the high genotoxicity of the chemical compound and the threat of serious genetic consequences if it enters the environment.